STRATEGI PERGURUAN TINGGI DALAM UPAYA MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Huseno, Tun (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
Changes in the world are now entering the industrial revolution era 4.0, where the pattern of human life is based on information. Thus, preparing quality literature and being able to compete globally, and mastering technological development are important for everyone and important for the future of a country. The success of a country in facing the 4.0 industrial revolution is closely related to the innovations created by resources quality, so that universities must be able to answer challenges to face technological advances and competition in the world of work in the era of globalization. In creating innovative and adaptive resources for technology, it is necessary to adjust learning facilities and infrastructure in terms of information technology, the internet, big data analysis and computerization. Universities that provide learning infrastructure are expected to be able to produce graduates who are skilled in aspects of data literacy, technology literacy and human literacy. The breakthrough in innovation will lead to increased industrial productivity and the birth of technology-based startup companies, as many have emerged in Indonesia today. This paper examines the concepts, theories and implementation of human resource planning strategies in higher education in facing the industrial revolution era 4.0.